Advanced wastewater reclamation – a response of the municipal sector to climate change and water scarcity - Zawadzki, Piotr; Wiesner-Sękala, Marta (Instal, 2024)
This paper presents systematised information concerning advanced technologies for municipal wastewater reclamation in 15 selected facilities worldwide. The analysed plants include both low-capacity facilities, designed to service specific needs, as well as major wastewater reclamation plants that service entire communities or cities, where the daily output can reach even up to 500 000 m3/d. These facilities serve from 4 000 to even up to 2.3 million people equivalent. State-ofthe-art wastewater reclamation plants typically employ a combination of multiple treatment methods, such as physical (e.g. sand traps, filtration), biological (e.g. biological reactors, membrane bioreactors) and chemical (coagulation, flocculation). However, it is becoming more common for wastewater treatment plants to expand their processing systems with a tertiary wastewater recycling. These include filtration processes (e.g. sand or carbon filters), biological (e.g. biological activated carbon) and membrane, particularly microfiltration, ultrafiltration and reverse osmosis. Reclaimed water is primarily used for irrigating green space, recreational areas, crop cultivation in agriculture, as well as potable water.
Keywords: municipal wastewater; wastewater reclamation; advanced wastewater treatment; water scarcity; climate change; wastewater management